IDENTIFICATION OF LANDSLIDE HAZARD BOUNDARIES OF THE DNIPRO SLOPE NEAR MYKILSKA BRAMA, KYIV - Кріль, Т.В.; Стрельцов, А.О. (Institute of Geological Sciences, NAS of Ukraine, 2025)
For the first time, the landslide hazard boundaries for the Dnipro slopes near Mykilska Brama have been scientifically substantiated and established, both for current and forecast conditions, based on the position of the slip surface. The study was conducted using a risk analysis of landslide activation, considering additional soil moisture as a result of the impact of anomalous meteorological and technogenic factors. The position of the slip surfaces was supported by the normative safety factor. Their delineation was carried out based on mathematical modeling for three profiles on the slope under natural physical and mechanical properties and in the forecasted (saturated) state. The calculations were performed using the RocScience Slide 6 software package, employing the Janbu method for a circular cylindrical slip surface. The engineering-geological conditions of this slope are characterized as complex due to the presence of a layer of subsiding loess soils and slope angles ranging from 20° to 43°. Field observations recorded markers of erosion-gravitational processes, including the “drunken forest” and tension cracks. The main factor for the loss of equilibrium of the soils on the slope is overmoisturization, which may result from anomalous rainfall or the influx of technogenic water into the soils from water supply network leaks. According to calculations of the slope safety factor in the forecasted state, in this case, with soil overmoisturization, a decrease of 10.4–22.4 % was determined compared to the actual condition. The landslide hazard boundary, considering the impact of additional soil overmoisturization and the corresponding decrease in soil strength properties, shifted by 30 meters in the middle section towards the edge of the slope. The methodology presented in the studies for determining landslide hazard boundaries serves as a practical tool for establishing such boundaries along the entire length of the Dnipro slope in Kyiv. Identifying landslide hazards in two states allows for the differentiation of risk levels associated with the loss of equilibrium of the slope’s soil mass and material losses due to the activation of displacements.